HIV Voluntary Counseling and Testing Uptake and Associated Factors Among Sexually Active Men in Ethiopia: Analysis of the 2016 Ethiopian Demographic and Health Survey Data - Kabeta T (Dove Medical Press, 2020)
Teshome Kabeta,1 Merga Belina,2 Mamo Nigatu1 1Jimma University, Institute of Health, Faculty of Public Health, Department of Epidemiology, Jimma, Oromia, Ethiopia; 2Addis Ababa University, College of Natural and Computational Sciences, Department of Statistics, Addis Ababa, EthiopiaCorrespondence: Teshome KabetaJimma University, Institute of Health, Faculty of Public Health, Department of Epidemiology, Jimma, EthiopiaTel +251911794169Email tka1204@gmail.comBackground: Human immuno-deficiency virus (HIV) counseling affirms that people exercise the right to know their HIV status, which opens the gateway to care, treatment, and support for a person in need. HIV counseling and testing uptake among sexually active males in Ethiopia is too low. Moreover, existing studies were not done at country level and the contributing factors were not well studied. Therefore, the aim of this study is to determine the status of uptake and identify its correlates using the 2016 Ethiopia Demographic and Health Survey.Methods: Data on 12,688 participants were utilized in this study. Descriptive statistics and multilevel logistic regression were used to summarize the data and investigate the associations between predictors and HIV counseling and testing uptake.Results: The overall HIV voluntary counseling and testing uptake among sexually active men in Ethiopia was 45.69%; 95% CI [43.08%, 48.33%]. About 13% of the variation in the likelihood of being tested for HIV was due to the variation among the regions. On the other hand, age, religion, education, occupation, marital status, HIV knowledge, health insurance coverage, wealth status, risky sexual behavior, family planning discussion with health workers, owning a mobile, frequency of watching television, and listening to the radio were significantly associated with the uptake of HIV voluntary counseling and testing.Conclusion: HIV voluntary counseling and testing uptake in Ethiopia is still low and varies across the regions, which might hamper the ambitious plan of Ethiopia to end AIDS as a public health threat by 2030. Therefore, giving due consideration to scale up HIV knowledge to avoid risky sexual behavior, improving access to health insurance and media, and working on the significant modifiable sociodemographic determinants are worthy to boost HIV voluntary counselling and testing uptake, which is an integral component of the strategies to efficiently prevent and control HIV.Keywords: Ethiopia, risky sexual behavior, sexually active men, voluntary HIV counseling and testing